The direct cost burden of 13 years of disabling workplace injuries in the U.S. (1998–2010): Findings from the Liberty Mutual Workplace Safety Index. (December 2015) - Marucci-Wellman, Helen R.; Courtney, Theodore K.; Corns, Helen L.; Sorock, Gary S.; Webster, Barbara S.; Wasiak, Radoslaw; Noy, Y. Ian; Matz, Simon; Leamon, Tom B.
Abstract: Introduction : Although occupational injuries are among the leading causes of death and disability around the world, the burden due to occupational injuries has historically been under-recognized, obscuring the need to address a major public health problem. Methods : We established the Liberty Mutual Workplace Safety Index (LMWSI) to provide a reliable annual metric of the leading causes of the most serious workplace injuries in the United States based on direct workers compensation (WC) costs. Results : More than $600 billion in direct WC costs were spent on the most disabling compensable non-fatal injuries and illnesses in the United States from 1998 to 2010. The burden in 2010 remained similar to the burden in 1998 in real terms. The categories of overexertion ($13.6B, 2010) and fall on same level ($8.6B, 2010) were consistently ranked 1st and 2nd. Practical application : The LMWSI was created to establish the relative burdens of events leading to work-related injury so they could be better recognized and prioritized. Such a ranking might be used to develop research goals and interventions to reduce the burden of workplace injury in the United States. Highlights: The LMWSI is an annual metric based on workers compensation (WC) costs of the most disabling non-fatal workplace injuries. Between 1998 and 2010 the LMWSI grew by 38%, from $37.1 billion to $51.1 billion in nominal terms. After adjusting for inflation, the burden in 2010 was similar in real-terms to the burden in 1998. Even after adjusting for inflation, injuries for fall on same level category, cost America $2 billion more in 2010 than 1998. The burden of overexertion injuries still far outweighs any other cause